Intertextuality in Legislative and Private Legal Texts - Trabulsi, Dana Abdul Rahman; Yagi, Sane; Ssaydeh, Abdulfattah Abu (International Journal of Linguistics, 2021)
Intertextuality has always been examined narrowly in the legal sphere despite its paramount significance to the legal translation analysis and pedagogy. For quite some time, the notion of intertextuality was deemed as a literary tool that contributed significantly to the literary works of infamous authors, novelists and poets. Post to a wealth of research to substantiate the omnipresence of intertextuality in other disciplines in general and in legal texts in particular, findings have restricted the notion of intertextuality to quite few phenomena such as citation, cross references, legal judgments, quotations and assimilation. This study, on the other hand, is an attempt to bring other implicit forms of intertextuality in legal written texts to light, through providing evidence-based generalizations about the different forms of intertextuality that are, deliberately or inadvertently, omnipresent in legislative and private legal texts. The notion of intertextuality was broadened to include recurrent legal terminologies and salient syntactic features in contractual agreements. The rhetorical organization of several legislative texts, such as UAE Decree, UAE labor law and an executive order originated from the USA was also closely examined to establish the notion of intertextuality in the structure of such texts. The results revealed that contractual agreements share similar templates and rhetorical organization, and the same holds true for legislative texts. A set of legal terminologies were found to be commonly utilized in lease agreements, employment agreements and Power of attorneys despite their different origins. Finally, the uses of a number of syntactic features were rather remarkable in contractual agreements, such as the abundant use of modal verbs to express obligation and imply futurity.